TOURIST BEHAVIOR AND PERCEPTION OF THE IMPLEMENTATION OF HEALTH PROTOCOLS IN THE NEW NORMAL ERA (Bukittinggi Tourist City) (JURNAL ECONOMICA : Research of Economic And Economic Education, 2021)
Abstrak This study aims to see the behavior and perceptions of tourists in implementing health protocols for tourists visited the tourist city of Bukittinggi, West Sumatera. The population of the research is tourists visited the tourist city of Bukittinggi during the pandemic of covid-19 with a total of 100 correspondents. Data collection was carried out using questionnaires. The data were analyzed using the SEM approach with Partial Least Square (PLS) method. The results showed that the tourists’ behavior and perceptions had a significant effect on the implementation of health protocols.